Intrinsic-Extrinsic Motivation and Work Performance of Hotel and Spa Employee - I Putu Sudana Sunario Adi Putra; I Gede Mudana; I Ketut Sutama; Ni Made Sudarmini (International Journal of Glocal Tourism, 2020)
Purpose: This research is to know the application of intrinsic motivation and extrinsic motivation to improve the performance of employees of a 4 star hotel and spa in Kuta, Bali, Indonesia. Research methods: Data obtained through observations, interviews, and questionnaires for 52 employees of the hotel and spa. The sampling technique used is proportional stratified random sampling. The analysis technique used is multiple linear regression. Findings: Intrinsic motivation (X1) has a positive effect on performance with a beta coefficient value of 0.393 having a positive value and a significance value of 0.003. Extrinsic motivation (X2) has a positive effect on performance with a beta coefficient value of 0.362 having a positive value and a significance value of 0.000. The test results for F arithmetic show the value of F is 54,833 and the significance value is 0,000. Implication: It is expected that the company is able to carry out their duties properly in improving the performance of their employees, one of which is by motivating the employees.